Modeling of the generalized unified power flow controller (GUPFC) in a nonlinear interior point OPF. - Xiao-Ping Zhang
With the progress of installing the latest generation of FACTS devices, namely, the convertible static compensator (CSC), several innovative operating concepts have been introduced to the historic development and application of FACTS. One of the novel concepts is the generalized unified power flow controller (GUPFC) or multi-line UPFC, which can control bus voltage and power flows of more than one line or even a sub-network. The GUPFC should have stronger control capability than the UPFC. A mathematical model for the GUPFC consisting of one shunt converter and two or more series converters is developed and implemented in a nonlinear interior point OPF algorithm. Numerical results with various GUPFC devices based on the IEEE 30 bus system and IEEE 118 bus system demonstrate the feasibility as well as the effectiveness of the GUPFC model established and the OPF method proposed
Keywords: FACTS devices; IEEE 118 bus system; IEEE 30 bus system; Convertible static compensator; Generalized unified power flow controller; Mathematical model; Multi-line UPFC; Nonlinear interior point OPF; Nonlinear interior point OPF algorithm; Power flow control; Shunt converter; Voltage control